Ketidaktepatan Kode Sebab Dasar Kematian menjadi Penyebab Kerugian 600 Juta Dana di Unit ICCU RSUD dr Moh Saleh Probolinggo - Novitasari Novitasari; Dewi Rokhmah; Isa Ma’rufi (Multidisciplinary Journal, 2021)
The coding of the diagnosis is important for patient care, hospital management and research. However, coding accuracy is a major problem in the diagnosis process and its impact on hospital income levels. This study impacts the inaccuracy of the basic cause of death coding on the level of hospital income. Methods: Analysis of the accuracy of the diagnosis according to the mortality coding rules compiled in the Intruction Coding Manual of the World Health Organization (WHO), after which the percentage of losses is carried out in the Diagnosis Based on Indonesian Case system. Results: as many as 176 files were studied, 114 files or 65% of the diagnosis codes of the cause of death were incorrect, 57 files or 32% were correct, and 5 files or 3% of files were not coded, 65% of these inaccuracies contributed to hospital losses 40-75 % loss with the total loss received by the hospital was IDR 597,849,006 or nearly 600 million rupiah. Conclusion: the absence of a diagnosis of death increases hospital losses by more than 40% to 75%.